Rapid screening of microfibrillated cellulose structure through FTIR and principal component analsysis - Mohd Nor, Nor Fatin Nabila; Mohamed Azmin, Nor Fadhillah; Asnawi, Ani Liza; Jimat, Dzun Noraini; Abdullah, Sureena (IOP Publishing Ltd, 2021)
Analysis of FTIR spectra combined with multivariate statistical analysis technique specifically Principal Component Analysis was used for rapid screening of microfibrillated cellulose (MFC) structure. The current methods used to extract the MFC are by using the chemical and physical approaches. To date, most researchers focused on bench (lab) scale experiment to identify the structure of MFC. Lack of mathematical models focusing on this goal has motivated this project. Principal component analysis is applied to identify the chemical composition of the MFC. The dataset comprises FTIR spectra of 12 samples that comes from MFC with different particles sizes, 200 µm, 250 µm and 800 µm. The result shows that the wavelength region which represents the MFC structure is in the range of 2950 cm-1 to 2978 cm-1 for particle size of 200 micrometer since it has larger surface area for penetration of fungal into the biomass due to lower diffusion of air, water and metabolite intermediates of which cellulose can be easily hydrolyzed due to increase in pore size of substance through greater removal of hemicellulose and lignin. The overall result indicates that the combination of FTIR analysis and PCA is a useful technique for rapid screening of MFC structure.